Implementation Of Marketing Mix Strategy 4P in With Love Milli Business - Shafa’ Annisa Puspasari; Nida Adenia Rahma; Muhammad Nashirul Haq; Sudarmiatin Sudarmiatin (International Forum of Researchers and Lecturers, 2024)
In the contemporary business environment, which is prone to competition, marketing can be considered as a series of structured business activities to plan, produce, price, promote, distribute goods, services, and ideas. The marketing mix is considered as one of the most important aspects of the marketing process, especially in MSMEs which are now growing very rapidly. This study was conducted with the aim of determining the marketing mix in the with love milli business which is used to drive product sales and create competitive advantages. This study uses a qualitative descriptive method that uses data collection techniques in the form of in-depth and structured interviews and observations. Based on the results of the interview, with love milli has implemented a marketing mix (product, price, promotion, place) to create competitive advantages and increase sales.